Monitoring and evaluating radio in education - McBurnie, Chris (EdTech Hub, 2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707898 2129771:E77BS5IR 2405685:PLW5MPU5
Keywords: _EdTechHub_Output; dode_eth-src-eth; dode_eth-trf2-dode

An EdTech reading list from the Helpdesk team: Autumn 2020 (EdTech Hub, 2020)
In this blog post, we summarise six new publications from the Helpdesk and what we have learned about monitoring and evaluation, curriculum reform, blended learning, and teacher education. As Covid-19 continues to affect learning around the world, our Helpdesk is seeing a shift in the requests we receive. Earlier, the bulk of requests were linked to short-term Covid responses. Now,…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707480 2405685:29RAGPFX 2405685:E2UQW73U
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Nine takeaways from our reviews of COVID-19 education responses - Chuang, Rachel; Kaye, Tom; Koomar, Saalim; McBurnie, Chris; Moss Coflan, Caitlin (EdTech Hub, 2020)
Regular readers will know about our Helpdesk, the on-demand support service we provide for FCDO advisers and World Bank staff to help them make evidence-informed decisions. Since the onset of coronavirus, the Helpdesk team has responded to requests from 15 countries across Africa, Asia, and the Middle…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707876 2405685:28EHRZSK
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707872 2405685:9EPB5ZXS
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
ZenodoArchiveID: 3469739 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3469739 2129771:IGCN5KBD 2339240:4DKQGFTT 2405685:25G275PG 2405685:L5TMC4NJ 2405685:YRC7UKWE
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707838 2405685:84ZQF884
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The role of interactive radio instruction in the coronavirus (COVID-19) education response - McBurnie, Chris (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Every week that passes we see the number of classrooms closed due to COVID-19 increase. During these unprecedented times, the Hub’s mission — to increase the use of evidence-based decisions around EdTech — is more important than ever. We must make sure learning goes on. […]
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707814 2405685:5ZVJ2YZ5
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The EdTech Hub’s Helpdesk and COVID-19: Demand-driven advice (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. With more than 1.5 billion children now affected by school closures, ministries of education and decision-makers around the world are urgently in need of fast, evidence-based, context-specific advice about out-of-school learning. Teachers, caregivers, parents and policymakers are tirelessly working to ensure that learning doesn’t stop. Faced with one of the…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707475 2405685:666VVKWG 2405685:AFE9INVN
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The Role of Interactive Radio Instruction in the COVID-19 Education Response - McBurnie, Chris (Open Development & Education, 2020)
Reading Time: 3 minutes At a time when the COVID-19 pandemic has forced over 1.5 billion students out of school, governments in resource-constrained countries have looked to interactive radio instruction (IRI) to ensure educational continuity. In the past week, we spoke with the Rising Academy Network to consider what an IRI programme could look like and why policymakers have […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707808 2405685:PBKNDCEU
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Learning through television in low-income contexts: mitigating the impact of coronavirus (COVID-19) - Watson, Joe (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Written by Joe Watson, research assistant at the University of Cambridge One of the many consequences of COVID-19 is that more than a billion caregivers will soon face the stark (and often scary) realisation that they must become their children’s teachers. This will be particularly difficult in low-income contexts where…
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707800 2339240:ELSHST8I 2339240:NH74Q4D5 2339240:SEDLSMKA 2339240:SRTNHXEM 2339240:ZL8JVQGI 2405685:54S7693K 2405685:BGP7GCNU 2405685:DLE5F2DK 2405685:FF93KYQR 2405685:LA5D6QFR 2405685:PCDTZ7S3 2405685:PD7SX3IX 2405685:SS7E2HN4 2405685:VCLDWRIS 4803016:U4W8F4AZ BGP7GCNU SEDLSMKA
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH